Nepali Ukhan Tukkako Sangkalan ra Adhyaanka Prarambhik Prayasharu: Sarvekshyan ra Bibechana - Subedi, Keshav (Tribhuvan University Journal, 2011)
Not available. Key words: Nepali Ukhan tukka; Nepali literature; Bibechana Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 139-148 Uploaded date: 21 April, 2011